A Case of Critical Calcified Innominate Artery Stenosis Successfully Treated With the Shockwave Lithoplasty. Issue 12 (February 2019) - Tripolino, Cesare; Grillo, Placido; Tassone, Eliezer Joseph; Morabito, Gaetano; Maselli, Daniele; Missiroli, Bindo
Purpose: The Shockwave Lithoplasty System represents a novel technology combining a balloon angioplasty catheter with the use of sound waves. Evidences suggest that it is a reliable tool to overcome calcified stenosis in both peripheral and coronary arteries. Here, we describe the case of a patient with calcified innominate artery stenosis successfully treated with the Shockwave Lithoplasty System. Case Report: A 78-year-old woman with hypertension, and dyslipidemia, came to our observation for dizziness. Instrumental examinations showed critical calcified stenosis of the innominate artery. The lesion was successfully treated with the Shockwave Lithoplasty System and subsequent stent apposition. Final angiography demonstrated excellent position of the stent, good wall apposition, and confirmed patency of the right common and right vertebral artery origins. Conclusion: Our clinical experience demonstrates that Lithoplasty is safe and effective also for the treatment of supra-aortic vessels.